Mec-Positive Staphylococcus Healthcare-Associated Infections Presenting High Transmission Risks for Antimicrobial-Resistant Strains in an Equine Hospital - Paula Soza-Ossandón; Dácil Rivera; Kasim Allel; Gerardo González-Rocha; Mario Quezada-Aguiluz; Ivan San Martin; Patricia García; Andrea I. Moreno-Switt (Antibiotics, 2022)
Healthcare-associated infections caused by Staphylococcus, particularly Staphylococcus aureus, represent a high risk for human and animal health. Staphylococcus can be easily transmitted through direct contact with individual carriers or fomites, such as medical and non-medical equipment. The risk increases if S. aureus strains carry antibiotic resistance genes and show a phenotypic multidrug resistance behavior. The aim of the study was to identify and characterize methicillin resistant coagulase-positive staphylococci (MRSA) and coagulase-negative staphylococci (MRCoNS) in equine patients and environmental sources in an equine hospital to evaluate the genetic presence of multidrug resistance and to understand the dissemination risks within the hospital setting. We explored 978 samples for MRSA and MRCoNS using Oxacillin Screen Agar in an equine hospital for racehorses in Chile, which included monthly samples (n = 61–70) from equine patients (246) and hospital environments (732) in a one-year period. All isolates were PCR-assessed for the presence of methicillin resistance gene mecA and/or mecC. Additionally, we explored the epidemiological relatedness by Pulsed Field Gel Electrophoresis (PFGE) in MRSA isolates. Phenotypic antibiotic resistance was evaluated using the Kirby-Bauer disk diffusion method. We estimated the unadjusted and adjusted risk of acquiring drug-resistant Staphylococcus strains by employing logistic regression analyses. We identified 16 MRSA isolates and 36 MRCoNS isolates. For MRSA, we detected mecA and mecC in 100% and 87.5 % of the isolates, respectively. For MRCoNS, mecA was detected among 94% of the isolates and mecC among 86%. MRSA and MRCoNS were isolated from eight and 13 equine patients, respectively, either from colonized areas or compromised wounds. MRSA strains showed six different pulse types (i.e., A1–A3, B1–B2, C) isolated from different highly transited areas of the hospital, suggesting potential transmission risks for other patients and hospital staff. The risk of acquiring drug-resistant Staphylococcus species is considerably greater for patients from the surgery, equipment, and exterior areas posing higher transmission risks. Tackling antimicrobial resistance (AMR) using a One Health perspective should be advocated, including a wider control over antimicrobial consumption and reducing the exposure to AMR reservoirs in animals, to avoid cross-transmission of AMR Staphylococcus within equine hospitals.